The Influence of Culture on Maternal Soothing Behaviours and Infant Pain Expression in the Immunization Context - Jillian Vinall; Rebecca Pillai Riddell; Saul Greenberg (Pain Research and Management)
OBJECTIVE: To investigate how maternal culture (ie, individualist versus collectivist) influences soothing techniques and infant distress.